Pengembangan LKPD Berbasis Project Based Learning (PjBL) Berbantuan Augmented Reality Materi Siklus Hidup Makhluk Hidup untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa Kelas IV SD - Tara Dika Utama; Endang Widi Winarni; Gumono (Jurnal Kajian Pendidikan Dasar, 2026)
This study aims to develop a PJBL worksheet assisted by Augmented Reality. This research is a development study using the ADDIE. The subjects of this study are: fourth-grade Based on data analysis, the results obtained are as follows: (a) the validation results by content experts ranged from 0.8 to 1.00 with a valid category. The validation results by language experts were 1 with a very valid category. Tthe validation results by graphic experts were 0.83 with a valid category (b) The results of teacher and student responses were very practical. (c) The average N-Gain score for the implementation class is 74.02%. The results of measuring creative thinking skills on the developed LKPD in the aspect of fluency showed an average posttest score of 19.76 and an average pretest score of only 6.36. The aspect of flexibility had an average posttest score of 27.26 and an average pretest score of only 9.73. The aspect of originality had an average posttest score of 36.8 and an average pretest score of only 7.6.So the conclusion of this study is that Project-Based Learning (PJBL) worksheets assisted by Augmented Reality are feasible to use, receive very positive responses, and can enhance students' creative thinking.